Social Representations of Family Health Strategy professionals on domestic violence against women (Research, Society and Development, 2020)
The objective was to analyze the structure and content of social representations about domestic violence against women, elaborated by professionals from the Family Health Strategy. Qualitative research based on the structural approach of the Theory of Social Representations, carried out with the teams of the Family Health Strategy of a municipality in Bahia, Brazil. For data collection, we used the technique of free evocations and semi-structured interviews; the treatment of the data had the collaboration of the software Ensemble of Programs Permettant 1 ’Analyzes des Evocations, version 2005. The prototypical analysis and similarity analysis by co-occurrence was used for the data from the free evocations; for the interview, content analysis. It is noted that the possible structure of the central nucleus of the professionals of the Family Health Strategy on domestic violence against women is based on the terms aggression, disrespect and cursing, characterizing the forms of violence identified by the professionals. The similarity analysis seeks to validate part of the findings of the prototypical analysis, pointing out the term lack of love as belonging to the central nucleus. There is an urgent need for training health professionals to care for women in situations of domestic violence, aiming at comprehensive care.